Successful cleavage of cloned goat embryos using ear fibroblast cell and fetal fibroblast cell as donor karyoplast in interspecies SCNT - SHARIF, SITI HASLINDA MOHD; AMRI, ASDIANA; WAN EMBONG, WAN KHADIJAH; ABDULLAH, RAMLI BIN (The Indian Journal of Animal Sciences, 2018)
The efficiencies in producing cloned ruminant embryos and subsequent production of offspring are still low. The study was conducted to produce cloned goat and cattle embryos using inter- and intraspecies SCNT techniques. This study involved 3 different types of donor karyoplast using goat and cattle oocyte as a recipient cytoplast to produce cloned goat and cattle embryos. The results showed that fetal fibroblast cell (FFC) in interspecies SCNT gave significantly higher 2-cell (64.40 vs. 38.43%), 4-cell (54.24 vs. 24.60%), 8-cell (36.82 vs. 14.54%) and morula (22.10 vs. 7.90%) cloned goat embryos than ear fibroblast cell (EFC). As for intraspecies SCNT using cumulus cell (CC) as a donor karyoplast to produce cloned cattle and goat embryos, the values for cleavage rates were not significantly different which were; 53.57 vs. 57.17%, 33.17 vs. 46.40%, 22.15 vs. 27.30% and 11.90 vs. 15.59%, respectively for all embryo stages. Our results showed that cloned goat and cattle embryos could be produced using different types of donor karyoplast in intra- and interspecies SCNT. However, for goat-cattle interspecies SCNT, FFC was more efficient to produce cloned goat embryos compared to EFC.